Multi-zone marine protected areas: Assessment of ecosystem and fisheries benefits using multiple ecosystem models. (1st August 2020) - Corrales, X.; Vilas, D.; Piroddi, C.; Steenbeek, J.; Claudet, J.; Lloret, J.; Calò, A.; Di Franco, A.; Font, T.; Ligas, A.; Prato, G.; Sahyoun, R.; et al.
Abstract: The current alarming state of many coastal ecosystems and fisheries calls for the development of tools to support recovery of exploited stocks, ensure their sustainable exploitation and protect marine ecosystems. Multi-zone Marine Protected Areas (MPAs) are often advocated to reconcile conservation and fisheries benefits. However, while there is a consensus about the ecological benefits whether such types of MPAs can really provide both benefits is still uncertain. Here, we analysed three existing Northwestern Mediterranean multi-zone MPAs (Cerbère-Banyuls, Cap de Creus and Medes Islands) using a comparative temporal ecosystem modelling approach to assess their effectiveness over time in recovering marine resources and ecosystem in the area. Our results showed differences in the ecological effectiveness of the three MPAs, potentially driven by MPA design, management and implementation features. Temporal increases of benefits were small, whenever detected, and showed slight recoveries of some target species and ecological indicators, mostly in Cerbère-Banyuls and Medes Islands MPAs. Our results confirm the benefits of protection to coastal marine resources and ecosystems when MPAs are enforced but highlight the current limitations of the three MPAs due to their small size and the significant impacts of small-scale and recreational fisheries. This study illustrates the capability to evaluate protection effects of small multi-zone MPAs with an ecosystem modelling perspective and represents the baseline to develop future scenarios of alternative management options to foster ecosystem recovery and resource rebuilding in the studied MPAs. Graphical abstract: Image 1 Highlights: We analysed three existing Northwestern Mediterranean multi-zone MPAs. We used a comparative temporal ecosystem approach. Our results showed differences in the ecological effectiveness of the three MPAs. Our results showed slight recoveries of some target species and ecological indicators. Our results highlighted the current limitations of the three MPAs.